Utilização de simulações computacionais como ferramenta de desenvolvimento de produto em indústria de alto-falantes - Skalee, John William (2015)
The present study is focused on product development and aims to verify the benefits of the use of computer simulation as a design tool in the industry speakers. For this reason every stage of a product development company in the speakers will be analyzed comparing the traditional method, which uses interactions between prototypes and experiments with the organization based on computational modeling philosophy. Computer modeling will be performed using the finite element method. It is known that with the fierce market competition, organizations are seeking alternatives in tools, processes and technologies that will bring some difference and add value to the final product, and thus differentiate itself from competitors. As a premise for the use of computer simulations, the characterization of the mechanical properties of the materials used in making the speaker is required. Therefore, the paper also proposes to implement a method capable of accurately obtaining the necessary mechanical properties such as Young s modulus, damping, density, etc. Although the study is focused on an industry speakers, this research also applies to organizations that have the stage of product development in their deal flow. Through this comparison methods, the research aims to enable managers responsible for product development, the pursuit of sustainable growth by enhancing the competitive position and reducing the vulnerability of their stay in the market. In this sense we propose a case study, evaluating methods, the feasibility and benefits generated through computational modeling, always seeking opportunities that aim to ensure the creation of value for the product and hence to the end customer.